Analisa Pengaruh Guest Experience terhadap Guest Satisfaction pada Hotel Majapahit Surabaya Managed by Accorhotels - Marcus Remiasa; Laurensia Giovanni Chandra; Deska Andriani Koentjoro (Syntax Corporation Indonesia, 2025)
This study was conducted to obtain empirical evidence of the influence of guest experience on guest satisfaction at Hotel Majapahit Surabaya Managed by AccorHotels. The research sample consisted of 105 respondents who were drawn using the purposive sampling technique. The respondents were guests who had stayed at Hotel Majapahit Surabaya Managed by AccorHotels. The research hypothesis was tested using multiple linear regression analysis techniques with the help of SPSS version 23. In this study, the dependent variable is guest experience, consisting of 3 components, namely Service product, Servicescape and Service Delivery System, and the independent variable is guest satisfaction which is measured by a likert scale of 1 to 5. The results of this study prove that: 1) overall guest experience has an effect on guest satisfaction, 2) Servicescape has a positive and significant effect on guest satisfaction and. 3) Service products and Service Delivery System have no effect on guest satisfaction.